Mechanism of fabrication and nano-mechanical properties of α-lactalbumin/chitosan and BSA/κ-carrageenan nanotubes through layer-by-layer assembly for curcumin encapsulation and determination of in vitro cytotoxicity. (August 2019) - Maldonado, L.; Chough, S.; Bonilla, J.; Kim, K.H.; Kokini, J.
Abstract: An exciting technology which still has many unknowns is the fabrication of hollow cylindrical polyelectrolyte complexes that can function at different pHs. With two-open ends and hollow interior, bionanotubes can find application in nanodevices, pharmaceutics, and biology. This study focused on fabricating nanotubes using chitosan (CHI) with α-lactalbumin (LAC), and bovine serum albumine (BSA) with κ-carrageenan (CAR). The ζ-potential charge difference was largest and therefore optimum at pH 7.0 for CHI/LAC and pH 4.0 for BSA/CAR. Strong electrostatic interactions enable the formation of bilayers from oppositely charged polyelectrolytes. ITC was able to show differences in the strength and spontaneity of electrostatic bonding interactions between both pairs of polyelectrolytes at these pHs. Nanotubes with 400, 600 and 800 nm diameter were achieved with a total of 5 bilayers for the 600 and 800 nm diameter nanotubes and 4 bilayers with the 400 nm diameter nanotubes using polycarbonate membranes. SEM images showed the formation of well-defined nanotubular structures that were affected by the type of polyelectrolytes used. The mechanical strength of the walls of the nanotubes was dependent on the polyelectrolytes used and the diameter of each nanotube, as shown by atomic force microscopy (AFM). Young's moduli, in the range of 25–55 MPa were obtained for LAC/CHI, and were significantly different from BSA/CAR nanotubes with values around 30–80 MPa. Both nanotubes systems proved to be potential candidates for the encapsulation and delivery of curcumin. These nanotubes achieved entrapment efficiencies around 40–45% with subsequent releasing in physiological conditions up to 300 μg/ml, with no significant cytotoxicity. Graphical abstract: Image 1 Highlights: Two types of nanotubes were fabricated with different diameters. Binding of both pairs of biopolymer was electrostatic and entropically driven. Nano-mechanical properties were affected by diameter and polyelectrolytes type. BSA/CAR nanotubes were more robust than LAC/CHI nanotubes. Curcumin encapsulation efficiencies were ∼40–45% and cell viability was ∼60–65%.